HUMAN CAPITAL AND PRODUCTIVE FORCES OF RURAL AREAS: ASPECTS OF ECONOMIC SECURITY OF THE STATE AND ITS REGIONS - PAVLOV, Kostiantyn; PAVLOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the interrelations between human capital, rural areas’ productive forces, and the country’s and its regions’ economic security. It underscores the pivotal role of human capital as the main factor determining the efficiency of using productive forces in rural areas. It demonstrates that the quality of labor resources, the level of education, and the vocational training of the population are not just important, but crucial for increasing labor productivity in the agricultural sector and ensuring food security. The article also analyses the key challenges faced by rural areas, including demographic changes, youth outmigration, and climate-related risks. It offers policy recommendations aimed at developing human capital and supporting rural areas’ productive forces. The article highlights the prospects for integrating these aspects into the overall strategy of ensuring Ukraine’s economic security, such as through targeted investment in education and healthcare, and the promotion of sustainable agricultural practices. The article is a valuable resource for developing policy solutions that can contribute to the sustainable development of rural regions and increase the state’s economic sustainability. Human capital is crucial for achieving sustainable economic growth and development. Investments in education, healthcare, and training are essential to increasing the population’s productivity and innovation. However, the efficient use of human capital requires creating conditions for its continuous development, adaptation to new technologies, and social equality. Rural areas’ productive forces are: an important element of the country’s economic system; ensuring food security protecting; natural resources, and ensuring the sustainability of the rural economy. To achieve sustainable development in rural areas, current challenges must be considered, and approaches to managing and managing productive forces must be applied to a crucial role in ensuring the economic security of the state through their significant contribution to food and environmental security, human capital development, and support for economic resilience. Rural areas play a vital role in the national security system by ensuring food and environmental security, contributing to human capital development, and supporting economic resilience. However, they face current challenges, such as demographic problems, climate change, and technological lag, which require active implementation of development strategies to preserve and strengthen the role of rural areas in the national security system. Strengthening the country’s economic security through rural development is not just an important task, but a critical one. Rural areas have the potential to significantly contribute to national security through diversifying economic activities, investing in infrastructure, increasing human capital, and ensuring environmental sustainability.